Social-Semiotic Analysis of Chupa Chups Printed Advertisement - Sutrisna Agustia, K T (KnE Social Sciences, 2019)
This research will emphasize the visual elements and layout of Chupa Chups ads in printed media that considered as a sign. Morrison (2007) explains that the basic components of printed media advertising can be called signs which consist of: headlines, advertisement agencies (text containing messages intended for ads readers, usually in the form of slogans or taglines), visual elements (brands, logos, color, photo, or illustrated image of the advertised product), and the layout used. This research is done by using qualitative approach by using social semiotics text analysis theory done by descriptive analysis on Chupa Chups printed advertisement. This ad is selected because it uses objects instead of human figures and interesting concept to representing it meaning. The analysis will describe all the marks on the ad while social semiotics focused on visual grammar. This research discusses 3 aspects of visual design meaning (Kress and Leeuwen, 2006) namely representational meaning, interactive meaning, and composition meaning. Found these 3 meanings are complementary in building the image of Chupa Chups product ads so that the purpose of the ad is well delivered to the readers. Keywords: advertisement, social semiotics, sign, meaning